Analisis Ukuran Perusahaan Dan Profitabilitas Terhadap Kualitas Laba Pada Perusahaan Sektor Industri Dan Kimia Di Bursa Efek Indonesia (Bei) - Khorida SE. AR (Simposium Nasional Mulitidisiplin (SinaMu), 2021)
This research analyze the effect of Firm Size  and Profitabilityon Earnings Quality in Manufacturing Companies in the Basic Industry and Chemical Sector 2016-2020. The research was conducted using a quantitative approach. The population in this study were basic industrial companies and chemicals listed on the Indonesia Stock Exchange (BEI) for the 2016-2020 period. The sampling technique used was purposive sampling, the samples obtained were 21 companies with 5 years of observation time, so the research data were 105 data. The analysis technique used is panel data regression with the help of E-Views 9.0 software. This study uses secondary data obtained from the website http://www.idx.co.id.The results show partially that firm size (SIZE) has a positive effect on earnings quality as evidenced by the t-statistic (2.079280)> t Table (1.98422) and the Prob value. (0.0402) <(0.05). And Profitability (ROA) t-statistic (-0.315333) < t Table (1.98422) and the Prob value. (0.7532)> (0.05). Keywords: Firm Size, Profitability, and Quality of Income